Meta-analysis of the effect of FLT3 inhibitor maintenance therapy on survival and chronic graft-versus-host disease in allogeneic hematopoietic stem cell transplantation for malignant hematologic disease: Meta-analysis of the effect of FLT3 inhibitor maintenance therapy - Li, Xin; Li, Lijun (Cellular and Molecular Biology, 2023)
This study aimed to investigate the effect of FLT3 inhibitor maintenance therapy on survival and chronic graft-versus-host diseases (cGVHD) in allogeneic hematopoietic stem cell transplantation (allo-HSCT) for malignant hematologic disease (MHD) by meta-analysis. For this purpose, Pubmed, Web of Science, Embase, and The Cochrane Library were searched for studies published up to April 2023. The search term was set as "FLT3 inhibitor". "allogeneic hematopoietic stem cell transplantation"; "malignant hematologic disease"; "chronic graft-versus-host disease". The literature was screened according to the inclusion and exclusion criteria, and then the data were extracted and analyzed by Revman5.3 software. Results showed that 9 eligible studies involving 964 patients were obtained. The relapse-free survival (RFS) of patients after treatment was analyzed by comprehensive model, odds ratio=3.28, 95% confidence interval (CI) = 1.76-6.11, Z=3.75, P=0.0002; Comprehensive model analysis of overall survival (OS), odds ratio=2.85, 95% CI= 2.12-3.83, Z=6.95, P <0.00001; Comprehensive model analysis of cGVHD, odds ratio=1.06, 95%CI = 0.37-2.98, Z=0.11, P=0.92. It was concluded that FLT3 inhibitor maintenance therapy could improve the RFS and OS of MHD patients treated with allo-HSCT but did not markedly affect the occurrence of cGVHD.